Development of the Northern Sea Route based on ESG principles - Smirnov Aleksey (E3S Web of Conferences, 2023)
The Northern Sea Route is the most important maritime logistics project. In the future, it should perform various, albeit interconnected, functions: transport support for extraction mineral resources in the Russian Arctic fields, transit communication between the ports of Europe and Asia, as well as the supply of cities and towns in the Arctic zone. At the same time, the future functioning of the Northern Sea Route should be based on the principles of ESG, aimed at minimizing environmental damage and rational use of labor resources. The purpose of the study is to determine the prospects for the development of the Northern Sea Route based on the ESG concept and propose measures to improve the efficiency of its operation. These measures include the development of a GIS system for monitoring the state of the environment in the area of the Northern Sea Route, and in the future, the transfer of all vessels to the use of natural gas motor fuel; development of a unified information system for managing northern delivery, which ensures the optimization of cargo flows; creation at the federal level of a forecasting system and monitoring of cargo transportation along the Northern Sea Route with a simultaneous strengthening of the responsibility of companies holding licenses for the extraction of minerals for the implementation of investment projects on time.